A GENRE-BASED ANALYSIS ON THE INTRODUCTIONS OF RESEARCH ARTICLES WRITTEN BY INDONESIAN ACADEMICS - Safnil Safnil (TEFLIN, 2013)
The main purpose of this study was to search for the occurrence of communicative and subcommunicative units and to identify the linguistic features commonly used by the authors to realize the communicative and subcommunicative units. Three groups of English RAs by Indonesian speakers were chosen for this study: 10 RAs from engineering science, ten from science and ten from medical science journals. This study used genre-based method to investigate the communicative units in the text by using Swalesâ CARS as a model. The results show that 1) only 11 out of 30 (36.66%) RA introductions have a âniche establishmentâ, 2) out of 11 RA introductionwith a niche establishment none is of counter claiming type, and 3) the discourse markers often used in the niche establishment are of the contradictory type and the linguistic features used are of lexical negation and negation of the phrasal verb. The findings confirm those of previous relevant studies that discourse styles and linguistic features of English RA introductions by Indonesianspeakers are different from the ones by English native speakers.